Decarbonization pathways of the Swiss cement industry towards net zero emissions. (15th March 2021) - Obrist, Michel D.; Kannan, Ramachandran; Schmidt, Thomas J.; Kober, Tom
Abstract: The present study investigates long-term energy consumption and CO2 emission pathways of the Swiss cement industry, including pathways towards net zero CO2 emissions by 2050. Cement production accounts for 8% (12.8 PJ) of the final energy consumption and 36% (2.5 Mt) of the CO2 emissions in the Swiss industrial sector in 2015. Using a techno-economic bottom-up optimization model based on the TIMES (The Integrated MARKAL-EFOM System) modeling framework, this study applies an advanced modeling technique for the Swiss TIMES Energy system Model (STEM) that expands the modeling of energy flows with additional material and product flow modeling. This allows a more detailed technology representation as well as to account for process related emissions in the cement sector. This modeling framework is applied for a scenario analysis focusing on energy efficiency as well as decarbonization, which ultimately contributes to an improved understanding of energy technology development and identifies policy strategies for the realization of a decarbonized cement industry. The results show that, in accordance with current trends, future cement production reduces its specific energy consumption from 3.0 GJ/tcement in 2015 to 2.3 GJ/tcement in 2050. Simultaneously, cement production decreases its CO2 emission intensity from 579 kgCO2 /tcement in 2015 to 466 kgCO2 /tcement in 2050 due to the decreasing average clinker content in cement and energy efficiency improvements. Even without major climate policy intervention in the future, it is economically beneficial to replace and improve the existing equipment with more energy efficient technologies. However, our results show that for a drastic reduction of the CO2 emissions in order to comply with the goals of the Paris Agreement, the cement sectors relies on CO2 capture because of the process related emissions. The results show that a minimum CO2 tax of 70 EUR/tCO2 is required for the CO2 capture technologies to become economically competitive.